Ask the beasts : Darwin and the god of love - Johnson, Elizabeth A., 1941- (2014)
For millennia, plant and animal species have received little sustained attention as subjects of Christian theology and ethics in their own right. Focused on the human dilemma of sin and redemptive grace, theology has considered the doctrine of creation to be mainly an overture to the main drama of humanity's relationship to God. What value does the natural world have within the framework of religious belief? The crisis of biodiversity in our day, when species are going extinct at more than 1,000 times the natural rate, renders this question acutely important. Standard perspectives need to be realigned; theology needs to look out of the window so to speak, as well as in the mirror. Ask the Beasts: Darwin and the God of Love leads to the conclusion that love of the natural world is an intrinsic element of faith in God and that far from being an add-on, ecological care is at the center of moral life. --
Beasts and entangled bank : a dialogue. Creation in and out of focus ; Models of engagement ; The weight of a theory ; A wager: good dialogue partners -- "When we look-- ". The author and his amazing book ; Core insight ; Science: special acts of creation ; A religious odyssey ; The beholder -- "Endless forms most beautiful". Starting with farm and garden ; Two key elements: variation and struggle ; The theory: natural selection ; The tree of life ; A crowd of difficulties ; Throughout time ; Across space ; Mutual affinities ; "There is grandeur in this view of life" -- Evolution of the theory. The center holds ; Misuse of the theory ; Scientific advances ; A cosmic lens ; An ecological lens -- The dwelling place of God. "We are fecund and exuberantly alive" ; Obstacles ; Life and love: a trinitarian framework ; Poetic biblical images ; The wisdom of philosophy: participation ; God's dwelling place -- Free, empowered creation. Paradigm of the lover ; The wisdom of philosophy: ultimate and proximate causes ; Interplay of law and chance ; Unscripted adventure ; Emergence: on behalf of matter and the body ; Beasts and entangled bank -- All creation groaning. "We suffer and die" ; Framing the issue ; Deep incarnation ; The Christic paradigm ; The cross and the tree of life ; Deep resurrection -- Bearer of great promise. Bookends ; "We are created" ; "We are finite and will end" ; Cosmic redemption ; Muir's bear -- Enter the humans. An evolving singularity ; Eaarth (sic) ; Extinction: never again ; The promise of nature ; Conversion to the earth -- The community of creation. "We are all creatures" ; The dominion paradigm ; The community of creation paradigm ; "Where were you...?" ; Creation's praise and lament ; The ecological vocation ; Onwards, for the love of God.
"A Continuum book"--Title-page verso.
Includes bibliographical references (pages 287-316) and index.
Keywords: Environmental degradation -- Religious aspects -- Christianity; Environmental protection -- Religious aspects -- Christianity; Nature -- Religious aspects -- Christianity